Augustine and time - Doody, John, 1943-; Hannan, Sean; Paffenroth, Kim, 1966- (Augustine in conversation., 2021)
This collection examines the topic of time in Augustine of Hippo. By placing Augustine into conversation with theologians and philosophers from the Islamic, Christian, and Buddhist traditions, the goal is to demonstrate the ongoing relevance of Augustine's account of temporality across historical, cultural, and religious boundaries.